The Attack Rate of Pocket Caterpillar (Metisa plana) And How To Control It on Oil Palm (Elaeis Guineensis Jacq) Plantation At PT Umada Pernantian â€œAâ€, North of Labuhanbatu Regency - Siallagan, Ricardo; Lestari, Widya; Adam, Dini Hariyati (Universitas Labuhanbatu, 2022)
Oil palm (Elaeis guineensis jacq.), is a vegetable oil-producing plant, which cannot be separated from the attack of caterpillars that eat oil palm leaves which can cause a decrease in plant production. The purpose of this study was to determine the attack rate of bagworm (Metisa plana) and how to control it, on each oil palm plant block at PT. Umada Pernantian